An MFS-Domain Protein Pb115 Plays a Critical Role in Gamete Fertilization of the Malaria Parasite Plasmodium berghei - Liu, Fei; Liu, Qingyang; Yu, Chunyun; Zhao, Yan; Wu, Yudi; Min, Hui; Qiu, Yue; Jin, Ying; Miao, Jun; Cui, Liwang; Cao, Yaming (Frontiers in Microbiology, 2019)
Sexual reproduction is an essential process in the Plasmodium life cycle and a vulnerable step for blocking transmission from the human host to mosquitoes. In this study, we characterized the functions of a conserved cell membrane protein P115 in the rodent malaria parasite Plasmodium berghei ANKA. Pb115 was expressed in both asexual stages (schizonts) and sexual stages (gametocytes, gametes, and ookinetes), and was localized on the plasma membrane of gametes and ookinetes. In P. berghei, genetic deletion of Pb115 (Δpb115) did not affect asexual multiplication, nor did it affect gametocyte development or exflagellation of the male gametocytes. However, mosquitoes fed on Δpb115-infected mice showed 74% reduction in the prevalence of infection and 96.5% reduction in oocyst density compared to those fed on wild-type P. berghei-infected mice. The Δpb115 parasites showed significant defects in the interactions between the male and female gametes, and as a result, very few zygotes were formed in ookinete cultures. Cross fertilization with the male-defective Δpbs48/45 line and the female-defective Δpfs47 line further indicated that the fertilization defects of the Δpb115 lines were present in both male and female gametes. We evaluated the transmission-blocking potential of Pb115 by immunization of mice with a recombinant Pb115 fragment. In vivo mosquito feeding assay showed Pb115 immunization conferred modest, but significant transmission reducing activity with 44% reduction in infection prevalence and 39% reduction in oocyst density. Our results described functional characterization of a conserved membrane protein as a fertility factor in Plasmodium and demonstrated transmission-blocking potential of this antigen.